USING PRECEDENT PHENOMENA IN ENGLISH AND RUSSIAN MEDIA - Маматкулова Камола (The Conference Hub, 2025)
At the present stage of development of the science of language, the fact that linguistic reality is closely connected with the world around us, its social norms and cultural values ​​is indisputable. The media contribute to the formation of these norms and the dissemination of values, designed not only to promptly report on everything new and interesting, but also to teach the reader, listener and viewer to perceive and correctly interpret the information received through various media channels.